2020
DOI: 10.1186/s12885-020-06799-0
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a five-immune gene prognostic risk model in colon cancer

Abstract: Background: Colon cancer is a common and highly malignant cancer. Its morbidity is rapidly increasing, and its prognosis is poor. Currently, immunotherapy is a rapidly developing therapeutic modality of colon cancer. This study aimed to construct a prognostic risk model based on immune genes for the early diagnosis and accurate prognostic prediction of colon cancer. Methods: Transcriptomic data and clinical data were downloaded from The Cancer Genome Atlas database. Immune genes were obtained from the ImmPort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 32 publications
0
36
0
Order By: Relevance
“…Colon cancer and primary liver cancer are common types of cancers in the digestive system (Grandhi et al, 2016;Chen et al, 2020). The expression of E-cadherin and vimentin is considered of high reference value in the prognosis of colon cancer.…”
Section: Effects On Digestive Diseasesmentioning
confidence: 99%
“…Colon cancer and primary liver cancer are common types of cancers in the digestive system (Grandhi et al, 2016;Chen et al, 2020). The expression of E-cadherin and vimentin is considered of high reference value in the prognosis of colon cancer.…”
Section: Effects On Digestive Diseasesmentioning
confidence: 99%
“…Previous studies have found that colon CSCs inhibit immune cells activity in the tumor microenvironment and led to the poor outcome of immunotherapy [37][38][39]. we used the ESTIMATE algorithm to infer immune score and explored the correlation between immune score and mRNAsi score and COAD stemness-related genes [40]. The immune scores were found to be negatively correlated with the mRNAsi scores and COAD stemness-related genes.…”
Section: Discussionmentioning
confidence: 98%
“…Studies have found that urotensin-II could contribute to breast carcinogenesis and Thr21Met polymorphism can be an important risk factor in developing breast tumors [38]. UTS2 might be used as potential targets to improve diagnosis and immunotherapy biomarkers for renal cell carcinoma and colon cancer [39][40].…”
Section: Discussionmentioning
confidence: 99%